Estudos de melhorias no processo de hidrólise enzimática de biomassas para produção de etanol - Corrêa, Luciano Jacob (2016)
In this work it was evaluated, firstly, the performance of four impellers configurations in the enzymatic hydrolysis of sugarcane bagasse. The configurations evaluated were: (1): Rushton turbine - Rushton turbine; (2): Elephant ear down-pumping and Rushton turbine; (3): Rushton turbine and Elephant ear up-pumping; (4): Elephant ear downpumping and Elephant ear up-pumping. The choice of the best impeller configuration was based in mixing efficiency, characterized by the mixing time. The configurations were also evaluated considering the conversion of cellulose to glucose, power consumption as well as the rheological behavior during hydrolysis. The hydrolysis experiments were carried out in batch stirred tank reactor (3 L) using 10% w/v of solids (pH 4.8; 50°C; 470 rpm), 10 FPU· g-1 biomassa for 96 h. The configuration (4) showed the lowest mixing time and energy efficiency values (ratio of conversion of cellulose to glucose and total energy consumption) of 78.9%·MJ-1. Further, to get a high concentration of glucose associated with low power consumption, it was investigated two operating modes: batch and fed-batch. The strategies evaluated were: E1 [20%]; E2 [10(E)+5+5%]; E3 [5(E)+5+5+5%]; E4 [5(E)+5+5+5%], and E5 5(E)+5(E)+5(E)+5(E)%]. The best energy efficiency was obtained for the E5 strategy in which substrate and enzyme were added simultaneously (0.35 kgglicose·kWh-1). This value was 52% higher than that obtained in the single batch operation (E1). In continuation of the work were carried out enzymatic hydrolysis of exploded and hydrothermal bagasse and cane straw submitted to hydrothermal pretreatment. The experiments were carried out under the conditions: solids loading of 10 (w/v), pH 4.8; 50 ° C; 470 rpm and 10 FPU·g-1 biomass for 96 h. The efficiency obtained in the enzymatic hydrolysis of steam explosion sugarcane bagasse proved to be 41 and 46% higher than the hydrolysis of hydrothermally pretreated sugarcane straw and bagasse, respectively. Finally, a scale-up protocol with a scale factor equal to 1000 was proposed. It was analyzed the maintenance of two parameters on larger scale: the constancy of the mixing time (tm) and the constancy of the power consumption per unit volume (P/V). In turn, maintenance P/V parameter constant, the mixing time and the new scale power consumption (3000L) were approximately 4 and 1000 times higher, respectively, than those values obtained in the smaller scale (3L).